"Go With the Flow": Independent Older Adults and Their Information-Seeking - Wicks, Don A. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Those in the growing older population in Canada and the United States deal with significant changes in their lives which complicate their information seeking. Work and social roles, technology and other factors in their lives change, requiring older adults to make adjustments in their information seeking behavior. In this study the researcher extended the word reported to the CAIS 27th Annual Conference in 1999.